A Comparative Study On Corporal Punishment About Children,S Right To Legal Protection - Khanikar, Monalisa; Bhattacharjee, Baloy (Journal of Neonatal Surgery, 2025)
Corporal punishment is a widely discussion topic globally with some countries banning it entirely, while others still permit it. This comparative study aims to examine the laws, policies, practices related to corporal punishment in different countries and their impact on children’s protection. Legal protection from all violent punishment is not only to protect the childrens from violence but also to raising their social status. Laws which allow adults to inflict violence on children in the name of “discipline” reiterated as a form of punishment. Laws are to ensure that children can no longer be lawfully subjected to violent punishment marks a turning point in society’s relationship with children, while giving recognition of children as human beings and rights holders. In enhancing children’s position in society, it advances all their other rights.